Occurrence of double primary malignancies in an African renal transplant recipient - Pavithra Mohan; Anand Yuvaraj; Georgi Abraham; Abraham Kurien; Anila Abraham; Milly Mathew; S Saravanan; Sanjeev Nair (Saudi Journal of Kidney Diseases and Transplantation, 2016)
A 63-year-old African male with end stage renal disease who received a renal transplantation from his daughter after successful treatment of hepatitis C virus, type 1 genotype developed metastatic Kaposi′s sarcoma and subsequently adenocarcinoma of the prostate. He was successfully treated with chemotherapy and reduction of immunosuppression and switch over to rapamycin.